Trends and Variability of Global Fire Emissions Due To Historical Anthropogenic Activities. Issue 1 (17th January 2018) - Ward, Daniel S.; Shevliakova, Elena; Malyshev, Sergey; Rabin, Sam
Abstract: Globally, fires are a major source of carbon from the terrestrial biosphere to the atmosphere, occurring on a seasonal cycle and with substantial interannual variability. To understand past trends and variability in sources and sinks of terrestrial carbon, we need quantitative estimates of global fire distributions. Here we introduce an updated version of the Fire Including Natural and Agricultural Lands model, version 2 (FINAL.2), modified to include multiday burning and enhanced fire spread rate in forest crowns. We demonstrate that the improved model reproduces the interannual variability and spatial distribution of fire emissions reported in present‐day remotely sensed inventories. We use FINAL.2 to simulate historical (post‐1700) fires and attribute past fire trends and variability to individual drivers: land use and land cover change, population growth, and lightning variability. Global fire emissions of carbon increase by about 10% between 1700 and 1900, reaching a maximum of 3.4 Pg C yr −1 in the 1910s, followed by a decrease to about 5% below year 1700 levels by 2010. The decrease in emissions from the 1910s to the present day is driven mainly by land use change, with a smaller contribution from increased fire suppression due to increased human population and is largest in Sub‐Saharan Africa and South Asia. Interannual variability of global fire emissions is similar in the present day as in the early historical period, but present‐day wildfires would be more variable in the absence of land use change. Key Points: The introduction of multiday burning into the model increases model fire interannual variability Historical land use change increases area burned but decreases fire emissions Recent land use change led to decreased global wildfire interannual variability